Living wages across the Pacific Rim: A localised replication study from China. (2020) - Hu, Yuting; Carr, Stuart C.
Theoretically, a living wage is a threshold that, once crossed, may transform qualities of work life, including from wage injustice to justice, organizational disengagement to commitment, and life dissatisfaction to satisfaction. Initial studies from New Zealand, South Africa and Thailand have found a threshold-like cusp in the relationship between wages and quality-of-work-life. Our aim in this study was to explore whether we would replicate a cusp in a localized study within China, among 135 employees in Shandong Province, Northern China. Survey data used minimal assumption and exploratory techniques to probe links between levels of employees' (1) take-home wage and (2) net household income; and (3) perceived wage justice, (4) commitment to employing organization, and (5) life satisfaction. Measures were locally aligned and statistically reliable. Consistent with living wage theory, as a participant's wage tended to cross a pay threshold of (1) RMB 4–5000 personally per month and (2) RMB 7–8000 household monthly, workers tended to report (3) wage justice (in place of injustice), (4) presence (replacing absence) of organizational commitment, and (5) satisfaction with life (replacing dissatisfaction). Our replication aim was met, but generalizing to any kind of national living wage across China would require a larger and more representative study and sample.